1971
DOI: 10.1039/j29710000577
|View full text |Cite
|
Sign up to set email alerts
|

The pyrolysis of 1,2-dichloroethane

Abstract: The pyrolysis of 1.2-dichloroethane in a static system has been studied by g.1.c. analysis of the products and by pressure measurements in the temperature range 340-51 5 "C, surface :volume ratio range (1 -32-37.4) cm-l, and with initial pressures from 0.3 to 300 Torr, in reaction vessels coated with pyrolytic carbon films.The major reaction is dehydrochlorination to vinyl chloride, but ethylene is also a primary reaction product. The ethylene yield is very small (<2% of the vinyl chloride) under conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The mole fraction of HCl, however, decreased slightly from 3 to 9 Torr. Minor product species with C-Cl bonds such as CCl 4 and C 2 HCl 3 increased slightly with pressure (Fig 3(C)). Other species without a C-Cl bond, except C 2 H 6 , decreased slightly with rising pressure.…”
Section: Effect Of the Operational Pressurementioning
confidence: 87%
See 2 more Smart Citations
“…The mole fraction of HCl, however, decreased slightly from 3 to 9 Torr. Minor product species with C-Cl bonds such as CCl 4 and C 2 HCl 3 increased slightly with pressure (Fig 3(C)). Other species without a C-Cl bond, except C 2 H 6 , decreased slightly with rising pressure.…”
Section: Effect Of the Operational Pressurementioning
confidence: 87%
“…4 Dyer and Matthews 5 have used a KrF laser to induce thermal decomposition of DCE. Kang et al 6 have also used a laser to induce the chain reaction of 1,2-dichloroethane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the decomposition of EDC have been worked under the thermal decomposition [Barton, 1949;Barton and Howlett, 1949;Howlett, 1952;Holbrook et al, 1971, Ranzi et al, 1992Incavo, 1996], the catalysed pyrolysis by chlorine or other species [Ashmore et ai., 1982a;Ashmore et al, 1982b], and the photolysis [Yano and Tschulkow-Roux, 1980;Ma et al, 1990;Cardy et al, 1993]. The thermal decomposition is one of the most widely used methods in commercial processes for the production of vinyl chloride.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of an induction period is also observed in the case of 1,2-dichloroethane which also exhibits an induction period when decomposed thermally. In the latter case, however, it has been shown that initiation probably occurs at the reaction vessel walls and the occurrence or absence of an induction period, i.e., the shape of the pressurehime curve, is markedly dependent on the extent and nature of the vessel surface [6]. The induction period may well result from the time taken for radicals produced at the walls to diffuse into the bulk of the gas.…”
mentioning
confidence: 98%